512 Trauma Meetings in the Time of COVID. (4th May 2021) - Hasan, R; Dhir, R
Abstract: Trauma & Orthopaedics (T&O) has taken a backseat during COVID-19. As the focus has shifted to care of COVID patients, other specialties have adjusted their daily working. At our local hospital, the dedicated Orthopaedic ward was absorbed into the Intensive Care department, necessitating migration to a smaller, shared working space. This project looked at ways of increasing clinical efficiency, patient safety and education within the T&O department. Members of the T&O department at The Princess Alexandra Hospital were invited to attend daily trauma meetings virtually via Microsoft Teams. In addition, the impact of moving to a larger, dedicated meeting space was assessed. Pre- and post-intervention questionnaires were delivered to assess response. Post-intervention questionnaires revealed a significant improvement in the perception of ability to see XRs (p < 0.001), quality of handover (p = 0.018), ability to discuss and formulate management plans (p = 0.002), social distancing (p < 0.001), location (p = 0.002) and trauma meetings overall (p < 0.000). The educational value of trauma meetings did not improve as anticipated, however. Virtual Trauma Meetings are a useful adjunct, allowing clinicians safely contribute to clinical care. In addition, the location of daily trauma meetings is an important factor to consider, both for the safety of patients and for the safety of clinicians.